Polymeric ligands comprising sulfur-containing amino acids for targeting tumor-associated amino acid transporters - Guo, Haochen; Xu, Wen; Nomoto, Takahiro; Kanamori, Kaito; Voon, Yan Ming; Honda, Yuto; Yamada, Naoki; Takemoto, Hiroyasu; Matsui, Makoto; Nishiyama, Nobuhiro (Biomaterials, 2023)
Various cancer cells overexpress L-type amino acid transporter 1 (LAT1) to take up a large number of neutral amino acids such as phenylalanine and methionine, and LAT1 transporter should be a promising target for cancer diagnosis and therapy. However, only a few studies reported drug delivery systems targeting LAT1 probably due to limited knowledge about the interaction between LAT1 and its substrate. Here, we developed polymers having methionine (Met)- or cysteine (Cys)-like structures on their side chains to examine their affinity with LAT1. While both the Met- and Cys-modified polymers exhibited efficient cellular uptake selectively in cancer cells, the Met-modified polymers exhibited higher cellular uptake efficiency in an LAT1-selective manner than the Cys-modified polymers. In the in vivo study, the intraperitoneally injected Met-modified polymers showed appreciable tumor-selective accumulation in the peritoneal dissemination model, and importantly, Met-modified polymers conjugated with photosensitizers exhibited significant therapeutic effects upon photoirradiation with reduced photochemical damage to normal organs. Our results may provide important knowledge about the polymer-LAT1 interaction, and the Met-modified polymers should offer a new concept for designing LAT1-targeting drug delivery systems.